Work Readiness of Transitional Society in Islamic View: A Study of Hawkers in the Mandalika Special Economic Zone - Suud, Suud; Malik, Imam; Masyhuri, Masyhuri; Sumitro, Sumitro (International Journal of Humanities, Education, and Social Sciences, 2025)
The development of the Mandalika Special Economic Zone (SEZ) has brought significant social and economic changes, influencing the rational choices of the surrounding transition communities, particularly hawkers. This study examines the level of rationality and skill readiness of hawkers affected by the tourism-driven transformation in the Mandalika circuit area and its buffer villages. Employing a qualitative approach through interviews and observations, the analysis reveals that hawkers’ rationality in adapting to economic shifts is shaped by factors such as knowledge, experience, work networks, and access to social and financial capital. The study also integrates Islamic perspectives, highlighting the principles of honesty (sidq), diligence (ijtihad), and responsibility (amanah) as critical values that enable traders to compete more effectively in a dynamic business environment. Findings provide insights into the adaptive strategies of the transitional community in the Mandalika SEZ and serve as a reference for policymakers to design support programs grounded in Islamic values, aimed at enhancing rational decision-making and skill preparedness in response to economic change.